Accidents with fireworks. Hand lesions in children. - Alves, R (1998)
We report our experience in the treatment and rehabilitation of traumatic hand lesions due to firework explosions. From January 1990 to January 1997, eight patients were evaluated according to the same protocol. All patients are from rural areas, males were predominant (87%) and ten years-old were the prevalent age group. The lesions were unilateral in 87.5% of all cases, with a special incidence in the left hand (55%) and the finger was the most affected, index (25.5%). Amputation was the most frequent residual lesion (75%), followed by debridement (62.5%) and changes intactil sensitivity (50%). Early surgery and rehabilitation are the fundamental aspects for the successful treatment and functional prognosis of these patients, but prevention is still the best way to stop the occurrence of these cases.